Cognitive Impairment in Patients with Chronic Neuropathic or Radicular Pain: An Interaction of Pain and Age - Moriarty, Orla; Ruane, Nancy; O'Gorman, David; Maharaj, Chris H.; Mitchell, Caroline; Sarma, Kiran M.; Finn, David P.; McGuire, Brian E. (Frontiers in Behavioral Neuroscience, 2017)
Background: A growing body of empirical research has confirmed an association between chronic pain and cognitive dysfunction. The aim of the present study was to determine whether cognitive function is affected in patients with a diagnosis of chronic neuropathic or radicular pain relative to healthy control participants matched by age, gender and years of education. We also examined the interaction of pain with age in terms of cognitive performance. Some limitations of previous clinical research investigating the effects of chronic pain on cognitive function include differences in the pain and cognitive scale materials used, and the heterogeneity of patient participants, both in terms of their demographics and pathological conditions. To address these potential confounds, we have used a relatively homogenous patient group and included both experimental and statistical controls. We have also specifically investigated the interaction effect of pain and age on cognitive performance. Method: Patients (n=38) and controls (n=38) were administered a battery of cognitive tests measuring IQ, spatial and verbal memory, attention and executive function. Educational level, depressive symptoms and state anxiety were assessed as were medication usage, caffeine and nicotine consumption to control for possible confounding effects. Results: Both the level of depressive symptoms and the state anxiety score were higher in chronic pain patients than in matched control participants. Chronic pain patients had a lower estimated IQ than controls, and showed impairments on measures of spatial and verbal memory. Attentional responding was altered in the patient group, possibly indicative of impaired inhibitory control. There were significant interactions between chronic pain condition and age on a number of cognitive outcome variables, such that older patients with chronic pain were more impaired than both age-matched controls and younger patients with chronic pain. Chronic pain did not appear to predict performance on the Wisconsin Card Sorting Task, which was used a measure of executive function. Conclusion: This study supports and extends previous research indicating that chronic pain is associated with impaired memory and attention.